The effect of a six-week home physiotherapy program on symptoms and activities of daily living in post-COVID-19 patients following hospital discharge (Journal of Health Sciences, 2024)
Introduction: Patients following the acute stage of Severe Acute Respiratory Syndrome Coronavirus 2 were shown to present with persisting symptoms including fatigue, dyspnea, joint pain, and chest pain. The aim of this study was to investigate the effect of a 6-week home physiotherapy program on the psychological and physical symptoms, as well as the physical abilities to perform activities of daily living in post-COVID-19 patients.Methods: The subjects were 39 adult patients who had been diagnosed with COVID-19 and had been hospitalized at the University Clinical Center of Kosovo. Patients initially underwent a physiotherapy assessment 2-3 weeks after discharge from the hospital, including sociodemographic data, psychological and physical symptoms, and functional performance in daily activities using the Patient-Specific Functional Scale (PSFS). Based on their functional capacity, the patients received two types of brochures for a home physiotherapy program that was carried out over the next 6 weeks. Upon the completion of the physiotherapy program, 23 patients reported for the second physiotherapy assessment. The Mann–Whitney Wilcoxon test was used for comparison of the variables obtained during the first and second assessments.Results: Pre–post analysis showed that the symptoms including excessive fatigue, difficulty breathing, and insomnia were significantly less present following the home physiotherapy program (p = 0.005; p = 0.008; p = 0.034). On the PSFS scale, the mean score increased from 5.2 (2.1) to 7.8 (0.5) for stair climbing, from 5.5 (1.8) to 8.8 (1.6) for walking longer distances, and from 3.7 (3.2) to 4.0 (5.6) for running.Conclusion: Although limited by the absence of a control group, the findings from this study indicate that home physiotherapy intervention can be feasible and effective in enhancing psychological and physical symptoms, as well as activities of daily living in post-COVID-19 patients following hospitalization.